Green technology an A-to-Z guide - Mulvaney, Dustin (Thousand Oaks, California London SAGE, 2011)
Featuring such disciplines as nanoscience, biochemistry, information technology and environmental engineering, in 150 articles this volume explores the essential role of technology in developments towards a sustainable environment.
Includes bibliographical references and index.
Keywords: Green technology; Sustainable engineering; Environmental engineering; Energy conservation; Electronic books